Evaluation of substrates, nutrient solution and rooting agent in tomato seedling production - Sandoval-Castro, Engelberto; Lazcano-Bello, María Isabel; Tornero-Campante, Mario Alberto; Hernández-Hernández, Brenda Nataly; Ocampo-Fletes, Ignacio; Díaz-Ruíz, Ramón (Revista Mexicana de Ciencias Agrícolas, 2021)
Obtaining high quality vegetable seedlings in seedlings allows producers to reduce the loss of seed, reduce the time to reach the optimum transplant height, minimize the loss of plants in soil or substrate and better adapt to the environment where the final transplant is performed. Producing seedlings in the best substrate and nutrition conditions increases the success of any crop. In most cases, imported substrates are used to produce seedlings in Mexico. For this reason, it is convenient to investigate alternatives of locally available substrates. The objective was to compare four substrates in two concentrations of the Steiner nutrient solution and a rooting agent in tomato seedlings (Lycopersicum esculentum Mill.) in the greenhouse. A factorial experiment with 16 repetitions was established in a completely randomized design. The variables were: days to emergence and appearance of the first true leaves, seedling height, stem thickness, number of leaves, fresh and dry weight of biomass and root. The results showed that the substrates that provided the best seedling quality characteristics were peat moss and tezontle, although there were no significant differences between 50% and 100%, to the nutrient solution, the concentration at 100% showed plants with higher quality and the rooting did not show a positive effect on the quality of the seedlings. Based on the above, the tezontle is recommended as a substrate to produce tomato seedlings because it is low cost, with a 100% Steiner nutrient solution, without applying a rooting agent.